Nanogel-crosslinked nanoparticles increase the inhibitory effects of W9 synthetic peptide on bone loss in a murine bone resorption model - Sato T (Dove Medical Press, 2015)
Toshimi Sato,1 Neil Alles,1,2 Masud Khan,1,3 Kenichi Nagano,1,4 Mariko Takahashi,1 Yukihiko Tamura,1 Asako Shimoda,5,6 Keiichi Ohya,1 Kazunari Akiyoshi,5,6 Kazuhiro Aoki1 1Department of Bio-Matrix (Pharmacology), Graduate School, Tokyo Medical and Dental University, Tokyo, Japan; 2Department of Biochemistry, Faculty of Medicine, University of Peradeniya, Peradeniya, Sri Lanka; 3Department of Dental Pharmacology, City Dental College and Hospital, Dhaka, Bangladesh; 4Department of Oral Medicine, Infection and Immunity, Harvard School of Dental Medicine, Boston, MA, USA; 5Department of Polymer Chemistry, Graduate School of Engineering, Kyoto University, Katsura, 6ERATO Akiyoshi Bio-Nanotransporter Project, Japan Science and Technology Agency, Katsura Int’tech Center Kyotodaigaku-Katsura, Nishikyo-ku, Kyoto, Japan Abstract: We investigated the biological activity of W9, a bone resorption inhibitor peptide, using NanoClik nanoparticles as an injectable carrier, where acryloyl group-modified cholesterol-bearing pullulan (CHPOA) nanogels were crosslinked by pentaerythritol tetra (mercaptoethyl) polyoxyethylene. Thirty 5-week-old male C57BL/6J mice were fed a low calcium diet and received once-daily subcutaneous injections of the carrier alone, W9 24 mg/kg/day alone, W9 24 mg/kg/day incorporated in cholesterol bearing pullulan (CHP) nanogels, or W9 (8 and 24 mg/kg/day) incorporated in NanoClik nanoparticles for 4 days (n=5). Mice that received a normal calcium diet with NanoClik nanoparticle injections without W9 were used as a control group. Radiological analyses showed that administration of W9 24 mg/kg/day significantly prevented low calcium-induced reduction of bone mineral density in the long bones and lumbar vertebrae, but only when the NanoClik nanoparticles were used as a carrier. Histomorphometric analyses of the proximal tibiae revealed that W9 24 mg/kg/day incorporated in NanoClik nanoparticles prevented the increase in bone resorption indices induced by a low calcium diet, which was confirmed by measurement of serum bone resorption markers. These data suggest that NanoClik nanoparticles could be a useful carrier for peptide therapeutics, and also demonstrate that daily subcutaneous injections of the W9 peptide with the nanoparticles were able to inhibit bone loss in vivo. An osteoclastogenesis inhibition assay performed in vitro confirmed a slower release profile of W9 from NanoClik nanoparticles compared with conventional CHP nanogels. Keywords: nanocarrier, peptide drug, injectable drug carrier, polyethylene glycol crosslinking, cholesterol-bearing pullulan, controlled release